A comprehensive analysis of time investment in skid trail planning for forest access - Marc Werder; Leo Gallus Bont; Janine Schweier; Oliver Thees (PLoS ONE, 2025)
Properly planned skid trails form an important basis for sustainable timber production. They affect cost-effectiveness and the environmental impact of the harvesting process to a large extent. Here, we conducted an economic analysis to understand the skid trail planning process and to generate an initial model to estimate the time and costs involved. We investigated in detail how the planning process of skid trails is carried out in practice, what time is required for the planning work, and what factors influence its performance. Through an online survey conducted in 2022, we asked practitioners in Germany and Switzerland about their time and effort required for the planning process and the determining factors, such as the planning method and the terrain and stand conditions. Based on this survey, we calculated statistical indicators of time consumption, considered possible rationalization options, and developed an initial estimation model. The effort required to identify and evaluate skid trails planned for distances of 20 to 40 m amounts to around 3 to 4 hours of productive working time per hectare, with deviations expected depending on the specific situation in the forest. The costs corresponding to this investment amount to less than one euro per cubic meter of harvested timber, depending primarily on the extent of wood use. Our in-depth insight into the planning process enables its economic evaluation and the development of improvements.